Orion and King Arthur - Bova, Ben, 1932- (New York : Tor, 2012)
Orion will battle the gods themselves to see that Arthur fulfills his destiny. But can even he save Arthur from the tragedy that awaits him?
"A Tom Doherty Associates book.&quot
Keywords: Orion (Fictitious character) -- Fiction; Time travel -- Fiction; Gods -- Fiction; Fantasy fiction; Fantasy fiction